Pan-cancer analysis of the prognostic and immunological role of Fanconi anemia complementation group E - Zhou, Zhixian; Yin, Huan; Suye, Suye; He, Jiarong; Fu, Chun (Frontiers in Genetics, 2023)
Fanconi anemia (FA) genes contribute to tumorigenesis by regulating DNA repair. Despite its importance for assembly and functionality of the FA core complex, no pan-cancer analysis of FANCE was performed. We aimed to provide a comprehensive understanding of the role of FANCE in cancers. Based on The Cancer Genome Atlas (TCGA), Cancer Cell Line Encyclopedia (CCLE), Genotype Tissue-Expression (GTEx), Human Protein Atlas (HPA), Gene Expression Omnibus (GEO), and Cancer Single-cell Atlas (CancerSEA) databases, we investigated the carcinogenicity of FANCE using various bioinformatics methods, including FANCE expression and prognosis, immune invasion, tumor mutation burden, microsatellite instability, and neoantigens. We monitored Fance mutations in mice that caused tumorigenesis. FANCE expression and activity scores were upregulated in 15 and 21 cancers. High expression of FANCE affected shorter overall survival (OS) in 7 cancers and longer OS in 3 cancers. It was correlated with shorter OS and progression-free interval (PFI) in endometrial cancer and longer OS and PFI in cervical cancer. FANCE expression negatively correlated with stromal/immune scores in 21 cancers including cervical cancer, endometrial cancer, and ovarian cancer. FANCE expression negatively correlated with CD8 T cells in endometrial cancer and positively correlated with M1 macrophages in cervical cancer, possibly related to cancer prognosis. FANCE positively correlated with immune checkpoint inhibitors PD-1, PD-L1, and CTLA4 in endometrial cancer and ovarian cancer. FANCE expression positively correlated with microsatellite instability, tumor mutational burden, and neoantigens in 7, 22, and 5 cancers, especially in endometrial cancer, potentially increasing the effectiveness of immunotherapy. Single-cell sequencing data showed FANCE was primarily expressed in cancer cells in cervical and ovarian cancer, and in fibroblasts in endometrial cancer. Fance heterozygous mutant mice had increased tumor incidences and shorter OS and tumor-free survival (TFS) than Fance homozygous mutant mice and wild-type mice. Conclusively, FANCE potential to serve as a biomarker for cancer prognosis and may predict cancer immunotherapy responses. Fance heterozygous mutant resulted in increased tumorigenesis and poor prognosis in mice.